Scientific Paper Entitled: The Reality Of Work Turnover In The Government Health Sector In The Kingdom Of Saudi Arabia And Its Impact On The Performance Of Health Personnel (Journal of Namibian Studies : History Politics Culture, 2022)
Turnover in the healthcare industry has gained international attention and is a major factor affecting how financially sound healthcare systems are. The problem has an impact on healthcare expenses, but it also affects accessibility and quality. One country that stands out for having a health care system plagued by high rates of employee turnover and intention to leave is Saudi Arabia. The most important factors influencing the departure of foreign healthcare professionals were discovered to be wage benefits and workload factors, closely followed by subpar hospital facilities and housing. The purpose of this study is to look into the factors that lead to employees' intents to leave their jobs as well as the connection between job satisfaction and work stress among Saudi Arabian healthcare workers.